2011
DOI: 10.1007/s10464-011-9451-0
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Help Community‐Based Organizations Implement an Evidence‐Based HIV Prevention Intervention: The Mpowerment Project Technology Exchange System

Abstract: Considerable resources have been spent developing and rigorously testing HIV prevention intervention models, but such models do not impact the AIDS pandemic unless they are implemented effectively by community-based organizations (CBOs) and health departments. The Mpowerment Project (MP) is being implemented by CBOs around the U.S. It is a multilevel, evidence-based HIV prevention program for young gay/bisexual men that targets individual, interpersonal, social, and structural issues by using empowerment and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
(34 reference statements)
0
25
1
Order By: Relevance
“…California, for instance, has defunded HIV prevention to the point that current programs are terminating and the ability to adopt new HIV prevention efforts is challenged [12]. Moreover, a handful of studies have found that economic factors influence the selection of specific HIV prevention programs, their implementation, and their termination [13][14][15]. Less is understood about how programs that experience reduced fiscal support adapt to sustain programs while attempting to continue implementation and, in turn, how those adaptations affect program fidelity.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…California, for instance, has defunded HIV prevention to the point that current programs are terminating and the ability to adopt new HIV prevention efforts is challenged [12]. Moreover, a handful of studies have found that economic factors influence the selection of specific HIV prevention programs, their implementation, and their termination [13][14][15]. Less is understood about how programs that experience reduced fiscal support adapt to sustain programs while attempting to continue implementation and, in turn, how those adaptations affect program fidelity.…”
Section: Overviewmentioning
confidence: 99%
“…Prior work examining HIV program fidelity has identified a number of fidelity challenges at the program level (e.g., training, client fit, procedural fit) [13,14,17,[24][25][26][27][28][29]. However, past studies have not examined how agencies adapt to economic strains and the influence of those adaptations on program fidelity.…”
Section: Program Fidelitymentioning
confidence: 99%
“…How do we motivate staff to request TA? Kegeles et al (2012) [25], in an implementation project for MPowerment, another CDC DEBI, provided proactive TA every two weeks. After six months, requests for TA increased and then remained high for as long as two years [25].…”
Section: Discussionmentioning
confidence: 99%
“…TA may be formally or informally provided, and includes advice, assistance and training pertaining to the implementation and maintenance of the program. Since then there are a number of studies which examine the conduct and monitoring processes of agencies funded to implement CDC DEBI packages [2024], but few have examined actual implementation of any DEBI program [1,25] and none have tested alternative, scalable approaches to disseminating these packaged interventions. At the same time, computer-assisted and Internet-based prevention programs have demonstrated better short- and long-term efficacy for a range of outcomes [2628] compared to manually based approaches, including HIV prevention risk reduction [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In a large study in the USA [32], the development of an intervention discussed; an intervention to help CBOs (communitybased organizations) implement the MP (Mpowerment Project, a community-level, evidence-based HIV prevention intervention for young gay/bisexual men that is a combination HIV prevention approach: small groups, community outreach, publicity, a drop-in center, and community mobilization). Mathematical modeling has demonstrated that MP is one of the intervention strategies with the potential to prevent the greatest number of new HIV infections in the US in a cost effective manner.…”
Section: Community-based Interventionsmentioning
confidence: 99%